Welding robots - Silva, Joaquim Norberto Cardoso Pires da (2003)
Using robots in industrial welding operations is common but far from being a streamlined technological process. The problems are with the robots, still in their early design stages and difficult to use and program by regular operators; the welding process, which is complex and not really well known and the human-machine interfaces, which are unnatural and not really working. In this article, these problems are discussed, and a system designed with the double objective of serving R&D efforts on welding applications and to assist industrial partners working with welding setups is presented. The use of object-oriented and distributed software to assist industrial robotic welding applications is discussed. The system is explained in some detail and demonstrated using two test cases that reproduce two situations common in industry: multilayer butt welding and multipoint fillet welding